Assessing Knowledge, Attitudes, and Practices on Dengue Fever among Patients in Central India: A Cross-Sectional Study - Siddhi Rathod; Ranjit Ambad; Hemant Juneja; Sarita Ugemuge; Gulshan Bandre (Journal of Pharmacy and Bioallied Sciences)
Background: Dengue fever is a major public health concern in India, with outbreaks occurring often and seasonally. This study analyzes general patients’ knowledge, attitudes, and practices (KAP) on dengue disease at a tertiary-care hospital in central India. Methods: A cross-sectional study was conducted with 300 general patients using a self-administered questionnaire. Descriptive statistics were computed, encompassing means, frequencies, percentages, and standard deviations. Results: Participants generally had positive attitudes towards dengue prevention. Many agreed on the importance of using mosquito repellents, maintaining clean environments, seeking medical help promptly, and supporting community mosquito control initiatives. Sociodemographic factors (age, gender, education level, and location) significantly influenced KAP and treatment adherence. Conclusions: This study provides valuable insights into the participants’ sociodemographic characteristics and their KAP regarding dengue fever.